2016
DOI: 10.1111/ecc.12467
|View full text |Cite
|
Sign up to set email alerts
|

Health professional's perspectives of the barriers and enablers to cancer care for Indigenous Australians

Abstract: To investigate health professionals' perspectives about factors that impede or facilitate cancer care for Indigenous people. Semi-structured interviews with 22 health professionals involved in Indigenous cancer care. Data were interpreted using an inductive thematic analysis approach. Participants presented their perspectives on a number of barriers and enablers to Indigenous cancer care. Barriers were related to challenges with communication, the health system and coordination of care, issues around individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…In addition, the implementation of dedicated care coordination has reduced incidences of delayed or cancelled surgery . A recent consensus statement from the National Heart Foundation for overcoming disparities between Aboriginal and non‐Aboriginal people in the management of acute coronary syndromes presents an argument for Aboriginal cardiac care coordinators to be incorporated into the health‐care system to liaise with service providers; review and monitor patients; communicate with families; ensure cultural factors are considered when organizing care; and to address social issues as patients move through the health‐care system …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the implementation of dedicated care coordination has reduced incidences of delayed or cancelled surgery . A recent consensus statement from the National Heart Foundation for overcoming disparities between Aboriginal and non‐Aboriginal people in the management of acute coronary syndromes presents an argument for Aboriginal cardiac care coordinators to be incorporated into the health‐care system to liaise with service providers; review and monitor patients; communicate with families; ensure cultural factors are considered when organizing care; and to address social issues as patients move through the health‐care system …”
Section: Introductionmentioning
confidence: 99%
“…In a previous Queensland study, care providers expressed similar concerns and identi ed a need for more culturally appropriate cancer information to assist care providers to communicate effectively and respectfully with Indigenous patients. 19 One patient in the current study suggested that training traditional healers to provide information on cancer and cancer treatment may empower communities to provide greater support to their members who require cancer care. A model of shared care involving traditional healers and Western physical and mental health practitioners has been demonstrated previously for remote Indigenous communities in Central Australia.…”
Section: Information and Communicationmentioning
confidence: 89%
“…The following factors have been identi ed over the past two decades as affecting Indigenous Australians access to CTS: di culties navigating the health system; low health literacy; logistical impediments; remote living location; gaps in care between primary and tertiary health services; [14][15][16] a historically-based wariness of government organisations; 17 fatalistic perceptions of cancer; 3,18 differing health paradigms; 19 cultural diversity; and language differences. 15,20 The extent to which CTS have adapted to overcome these and other barriers to improve access for Indigenous people is unclear and further research is needed to better understand and respond to issues of accessibility to CTS, particularly in more remote locations where people are likely to face multiple challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of health systems to adapt and deliver care in alignment with the needs and preferences of indigenous people continues to be a barrier (Meiklejohn et al . ) so does the potential to alienate patients and their families though poor communication (Brown et al . ; Zorbas & Elston ).…”
mentioning
confidence: 99%
“…A history of exposure to racism continues to impact negatively on the health of indigenous people, with papers in this issue continuing to highlight significant inequities in cancer outcomes for indigenous people in New Zealand (Robson & Ellison-Loschmann 2016), Canada (Beben & Muirhead 2016) and Australia (Zorbas & Elston 2016). The ability of health systems to adapt and deliver care in alignment with the needs and preferences of indigenous people continues to be a barrier (Meiklejohn et al 2016) so does the potential to alienate patients and their families though poor communication (Brown et al 2016;Zorbas & Elston 2016). Smoking underpins the high rates of lung and head and neck cancers.…”
mentioning
confidence: 99%